Membangun Generasi Sehat Melalui Edukasi Parenting untuk Pencegahan Stunting di Dusun Masangan - Dhohirrobbi, Achmad; Camelia Cahyani, Verisa; Wutsqa, Urwatul; Azzam, M. Abdullah; Anjani, Khofifah Tri; Afiroh, Siti; Dharma, Kusuma Sanata; Nugraha, Much. Azhar Fanza; Pusposari, Luthfiya Fathi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Stunting remains a major health challenge in Indonesia, particularly in lower-middle-income regions. The primary cause of stunting is chronic malnutrition during the first 1,000 days of life, exacerbated by poor hygiene and limited access to healthcare facilities. According to the 2022 Indonesian Nutritional Status Survey (SSGI), the national stunting prevalence is 21.6%, with East Java at 19.2%. If left unaddressed, stunting can negatively impact physical and cognitive development, as well as the overall quality of human resources in the future. As a preventive effort, the "Building a Healthy Generation through Parenting Education for Stunting Prevention in Dusun Masangan" program was conducted by the Vidhyadhyana KKN Group. This program aims to enhance parental understanding of proper childcare, balanced nutrition, and stunting prevention through educational approaches. The methods include counseling, parental assistance, and the involvement of posyandu cadres and community leaders in supporting child development. The results indicate an increase in participants' understanding of the importance of balanced nutrition and proper parenting. Activities such as child and elderly posyandu services, as well as outreach programs for pregnant and breastfeeding mothers, provided new insights and skills for families to maintain their health. This program is expected to foster a healthier, smarter, and more productive generation while reducing stunting rates in Dusun Masangan and surrounding areas.